KONDISI SOSIAL EKONOMI TENAGA KERJA PENAMBANG EMAS DI DAERAH DURIAN SIMPAI KECAMATAN SEMBILAN KOTO KABUPATEN DHARMASRAYA - Wardini, Pefti - (Pendidikan Geografi, 2014)
This Reseacht aims to determine the Socio-Economic Conditions Of Gold Mining Labor In Durian Simpai Sembilan Koto Subdistrict Of Dharmasraya Regency. This Reseacht is descriptive study. The population in this study were all workers who work as a labor mine in the area Durian Simpai. A total of 240 persons & determined by proportional random sampling technique with a 25% proportion of the workforce that is 60 gold mining. The instrument used in this study is questionnaire. Data analysis using the percentage. The results of this study are: 1) Labor Income Level Is Rp 2,000,000.- Rp 3,000,000.- with the percentage of 43.33% in a single trip, within one month of Labor Gold Miners worked as many as three trips with a percentage of 33.34%. additional income of Rp 5,000,00- Rp 1,000,000- with the percentage 43.33% in one week. So Labor Income Level Local Gold Mining In Simpai Durian can make ends meet with a percentage of 46.67%. 2) Tertiary Education Workforce Gold Mining generally College formal junior high with a percentage of 21.67%, however there are workers who completed high school with a percentage of 20%, and graduated from college with a percentage of 3.33%. 3) Workers Social Interaction Gold Mining. Labor of the ship goes well with the percentage of 78.33%, because of the labor to help each other with the percentage of 68.33%, The interaction of labor with a workforce of one ship another ship ever had a conflict with a percentage of 66.67% due to seizure Lobong with the percentage 48.33% and its solution by means of consultation with a percentage of 50%, labor Interaction with mine owners never had a conflict with a percentage of 53.34% due to the unequal distribution of salaries with the percentage of 56.67% and the solution to deliberate with the percentage of 53.33%.